Analytical modelling of flame transfer functions for technically premixed flames. Issue 1 (March 2022) - Biagioli, Fernando; Innocenti, Alessandro; Lamraoui, Ammar; Syed, Khawar J
The linear response to harmonic acoustic excitation of the total heat release rate in technically premixed flames (Flame Transfer Function, FTF) is studied in case of an ideal swirl burner. The analysis is based on the linearization of the production rate for the mean reaction progress variable modelled with a turbulent flame speed closure. Three main components of the FTF are identified which are generated by: I) direct fluctuations in the fuel mixture fraction (formation enthalpy contribution), II) direct fluctuations in the turbulent flame speed and III) flame surface area fluctuations driven by velocity and turbulent flame speed fluctuations. The velocity fluctuation is separated into an irrotational acoustic displacement and a rotational convective component. The effect of the rotational velocity component on the FTF is modelled here in a semi-empirical way, related to swirl number fluctuations at the flame base due to the phase shift between convected tangential velocity fluctuations and acoustically propagating axial velocity fluctuations. It is finally shown that fuel mixture fraction fluctuations can be generated not only by air mass flow rate fluctuations but also by fuel flow rate fluctuations which depend upon the air side impedance at the fuel injection location. It is shown that this impedance changes with the geometry of the plenum placed upstream the burner affecting in this way also the FTF.